Long-Term Outcome of Infantile Brain Tumors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Twenty seven consecutive patients diagnosed with brain tumor in the first year of life, between 1980 and 2005, were followed at the University Children's Flospital of Zurich, Switzerland.